980 Improving care for victims of violence in resource-poor settings such as Lusaka, Zambia. (1st September 2016) - Schober, Michael; Mtonga, Robert; Valenti, Maria; Hametner, Stephanie
Abstract : Background: Violence is a leading worldwide public health problem and obstructs achievement of the Millennium Development Goals. 90% of the global burden of violence and injury mortality occurs in low-income and middle-income countries. 35% of women worldwide have experienced physical and/or sexual intimate partner violence or non-partner sexual violence. In Zambia, gender-based violence against women and girls is widespread, with >50% of women reporting some form of abuse. Methods: Health professionals from Zambia and Austria conducted a low-cost intervention in Lusaka, Zambia, intended to improve care outcomes for victims of interpersonal violence (IPEV). It was designed to build on existing health and social services infrastructures. During 1 year, 174 victims of IPEV seen at the Lusaka University Hospital emergency room were interviewed. An intervention included training for medical and social service personnel and distribution at key locations of printed materials on services available to IPEV victims. Results: Postintervention data analysis revealed that victims of IPEV had improved understanding of available social services, and victims' confidence was increased about receiving additional help and articulating health concerns. Other benefits: improved visibility, networking among partner organisations; new descriptive data about IPEV victims; improved cross-cultural understanding among medical participants. Conclusions: Low-cost interventions may improve care for victims of violence in resource-poor settings. Improved cooperation among social service and medical providers may improve care for victims of IPEV and also benefit agencies through strengthened relationships and flow of information. North–South cooperation should be encouraged at the institutional level. Profiles of victims contribute to global data on violence. Recommendation: low-cost interventions should continue to be explored to improve care for victims of IPEV in resource-poor settings.